STUDY OF FOOD SAFETY ON DARK CHOCOLATE ENRICHED WITH CINNAMON (Cinnamomum burmanii) DURING STORAGE - Muhammad Isa D. & Danar Praseptiangga, Dimas Rahadian A.M.,Intan Nisa R., Anasta Ilmi, Yasmin Nabila (Proceeding of International Congress, 2014)
Fat and sugar blooming on chocolate affects on consumer acceptance, because the existing perceptionthat blooming decrease the safety of the product. Enriching dark chocolate bar with essential oil fromcinnamon (Cinnamomum burmanii) have been conducted. This research aims to investigate the effect ofcinnamon on the blooming occurence during storage. As soon as the chocolate bloomed, FFA and TPCanalysis were performed as safety indicator. The results shows that enriching essential oil from cinnamonslackens bloom appearance on dark chocolate. The bloomed product is safe to be consumed, since FFAand TPC number are under the maximum limit of the requirements of food safety.Keywords: dark chocolate, food safety, bloom, cinnamon